Advancing bone tissue engineering one layer at a time: a layer-by-layer assembly approach to 3D bone scaffold materials. (19th April 2022) - Sahebalzamani, MohammadAli; Ziminska, Monika; McCarthy, Helen O.; Levingstone, Tanya J.; Dunne, Nicholas J.; Hamilton, Andrew R.
Abstract : The combination of multilayers for multifunctional coatings in the application of layer by layer (LbL) assembly for bone tissue engineering (BTE). Abstract : The layer-by-layer (LbL) assembly technique has shown excellent potential in tissue engineering applications. The technique is mainly based on electrostatic attraction and involves the sequential adsorption of oppositely charged electrolyte complexes onto a substrate, resulting in uniform single layers that can be rapidly deposited to form nanolayer films. LbL has attracted significant attention as a coating technique due to it being a convenient and affordable fabrication method capable of achieving a wide range of biomaterial coatings while keeping the main biofunctionality of the substrate materials. One promising application is the use of nanolayer films fabricated by LbL assembly in the development of 3-dimensional (3D) bone scaffolds for bone repair and regeneration. Due to their versatility, nanoscale films offer an exciting opportunity for tailoring surface and bulk property modification of implants for osseous defect therapies. This review article discusses the state of the art of the LbL assembly technique, and the properties and functions of LbL-assembled films for engineered bone scaffold application, combination of multilayers for multifunctional coatings and recent advancements in the application of LbL assembly in bone tissue engineering. The recent decade has seen tremendous advances in the promising developments of LbL film systems and their impact on cell interaction and tissue repair. A deep understanding of the cell behaviour and biomaterial interaction for the further development of new generations of LbL films for tissue engineering are the most important targets for biomaterial research in the field. While there is still much to learn about the biological and physicochemical interactions at the interface of nano-surface coated scaffolds and biological systems, we provide a conceptual review to further progress in the LbL approach to 3D bone scaffold materials and inform the future of LbL development in bone tissue engineering.